Picturing the workers' olympics and the spartakiads : modernist and avant-garde engagement with sport in Central Europe and the USSR, 1920-1932 - Strożek, Przemysław (2023)
"This volume focuses on the modernist and avant-garde engagement with workers' sport events that were organised or were planned to be organised in the cities of Central Europe and the USSR in the period of 1920-1932: Frankfurt am Main - Vienna - Moscow - Prague - Budapest - Berlin. This volume is of great use to students and scholars of the history of sport, art history and cultural history in interwar Europe and the Soviet Union